Diseño e implementación de hojas de vida en Microsoft Access para los equipos biomédicos de Médicos Asociados S.A. en Liquidación (2023)
Médicos Asociados S.A. en Liquidación, was legally constituted since 1978 as a company dedicated to provide health services in the country; in spite of its long trajectory, as a consequence of the fall in its assets during the last years, it was dissolved and liquidated, a process that to date is still in force.